NALAR HUKUM ISBAT NIKAH DI PENGADILAN AGAMA KEDIRI - Pujo Pangestu; Habibi Al Amin (JURNAL HAKAM, 2023)
ABSTRACTA judge's legal reasoning is the main foundation in providing public service policies related to religion. Whether a judge actually gives a fair verdict or not, whether he is a person who understands very well the case to be decided or not, and whether he is religiously alim so that he is worthy of being a representation of religion and state or vice versa. Here the researcher examines one case as a representative of the picture, namely 1) What is the judge's consideration in the determination of marriage certificates in Judgment Number: No.3422/Pdt.G/2021/PA. Kab.Kdr? 2) Is there a religious basis that has been used as a handle (compilation of dalils) by the Religious Court as a basis for giving legal decisions? The results obtained are 1) The judge has given an exact verdict from the evidence that has been collected and is strong, only it is still weak in providing a foundation of religious rules. 2) The judge gives his ijtihad with the arguments that are curated so that each basis of the arguments used by the judge must differ between one judgment of the petitioner and the other petitioner in one similar case. From this research, at least there is a compilation of religious law arguments that are used as a basis by judges so that it will maintain the marwah of judges appointed by the state if they have limited time to find a basis for arguments to strengthen judges' decisions. Keywords: Marriage Certificates, Legal-Religious Propositions, Judges' Rulings, Religious Courts. ABSTRAKNalar hukum seorang hakim merupakan pondasi utama dalam memberikan kebijakan layanan publik terkait keagamaan. Apakah seorang hakim benar-benar memberikan putusan adil atau tidak, apakah dia seorang yang mengerti betul terkait kasus yang hendak diputus atau tidak, dan apakah ia memang benar-benar alim dalam agama sehingga layak menjadi representasi dari agama dan negara, atau sebaliknya. Di sini peneliti mengkaji satu kasus sebagai perwakilan gambaran, yakni 1) Bagaimana pertimbangan hakim dalam penetapan isbat nikah dalam Putusan Nomor: No.3422./Pdt.G/2021/PA.Kab.Kdr? 2) Adakah dasaran agama yang sudah dijadikan pegangan (kompilasi dalil-dalil hukum) oleh Pengadilan Agama sebagai landasan memberikan putusan hukum? Hasil yang diperoleh adalah 1) Hakim telah memberikan putusan yang tepat dari bukti-bukti yang telah dikumpulkan dan kuat, hanya saja masih lemah dalam memberikan landasan kaidah agama. 2) Hakim memberikan ijtihad sendiri dengan dalil-dalil yang dikuasai, sehingga setiap landasan dalil yang digunakan oleh hakim mesti berbeda antara satu putusan pemohon dengan pemohon lainnya dalam satu kasus serupa. Dari penelitian ini, setidaknya ada kompilasi dalil-dalil hukum agama yang dijadikan landasan oleh para hakim, sehingga akan menjaga marwah para hakim yang diangkat oleh negara apabila mereka memiliki keterbatasan waktu untuk mencarikan dasaran dalil sebagai penguat putusan hakim. Kata Kunci: Isbat Nikah, Dalil Hukum-Agama, Putusan Hakim, Pengadilan Agama.